2017
DOI: 10.1016/j.jand.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Meals Enhancing Nutrition After Discharge: Findings from a Pilot Randomized Controlled Trial

Abstract: Background After older adults experience episodes of poor health or are hospitalized, they may not return to pre-morbid eating behaviors. Furthermore, poor nutrition increases hospital readmission risk, but evidence-based interventions addressing these risks are limited. Objective The pilot study’s objective was to evaluate the feasibility of conducting a randomized controlled trial assessing a post-discharge home-delivered meals program’s impact on older adults’ nutritional intake and hospital readmissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Strategies to improve post-discharge nutrition-care may include referral to a community dietitian [ 16 , 17 , 18 ] either by having the patient attend a clinic or having the dietitian visit the patient at home [ 18 , 19 ]; use of oral nutritional supplements (ONS) when needed [ 20 , 21 ]; a combination of dietetic counseling and ONS [ 22 , 23 , 24 ]; meal delivery programs [ 25 , 26 , 27 , 28 ]; or education and recommendations provided in hospital prior to discharge, among others. Several of these interventions have been found to improve body weight and self-reported food intake, however many studies lack rigor [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to improve post-discharge nutrition-care may include referral to a community dietitian [ 16 , 17 , 18 ] either by having the patient attend a clinic or having the dietitian visit the patient at home [ 18 , 19 ]; use of oral nutritional supplements (ONS) when needed [ 20 , 21 ]; a combination of dietetic counseling and ONS [ 22 , 23 , 24 ]; meal delivery programs [ 25 , 26 , 27 , 28 ]; or education and recommendations provided in hospital prior to discharge, among others. Several of these interventions have been found to improve body weight and self-reported food intake, however many studies lack rigor [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In anticipation of this, we plan to allocate short-term funding for the provision of services (e.g., covering approximately 2 months of homedelivered meals) for at-risk patients immediately following ED or hospital discharge, if needed. This approach is consistent with other post-discharge nutrition interventions that provide home-delivered meals [38,39]. However, it is possible that some patients will return to a waitlist for services after the short-term funding is exhausted.…”
Section: Limitations and Challengesmentioning
confidence: 61%
“…Much of what we knew previously about the health and health care utilization of MOW clients came from participants’ self-report. 2326 The linkage of MOW program data to Medicare claims enables research into clients’ health and health care utilization, as well as costs to the Medicare program associated with enrollment in these programs that is not limited by potential response bias. Using these linked data, we confirmed that the sample of Medicare beneficiaries receiving MOW represent a vulnerable group with many comorbidities compared with that of Medicare beneficiaries in the surrounding service areas.…”
Section: Discussionmentioning
confidence: 99%